THE LEGAL STATUS OF THE EXECUTION OF WORKS BY DIRECT ADMINISTRATION - Yhon Cristian Barrionuevo Monzón (2020)
The article focuses on demonstrating that the execution of civil works by direct administration does not have a legal basis in Peruvian law, and is only based on custom and lack of control, specifically, it is supposed to demonstrate that the Comptroller's Resolution No. 195-88-CG has been tacitly repealed by article 76 of the 1993 Political Constitution of Peru.